Prospects of fundamental sciences development : selected, peer reviewed papers from the XI International Conference on Prospects of Fundamental Sciences Development (PFSD-2014), April 22-25, 2014, Tomsk, Russia - Kurzina, Irina; Godymchuk, Anna (Advanced materials research, 2015)
Collection of selected, peer reviewed papers from the XI International Conference Prospects of Fundamental Sciences Development (PFSD-2014), April 22-25, 2014, Tomsk, Russia. The 97 papers are grouped as follows: Chapter 1: Chemistry and Physics of Materials, Environmental Materials; Chapter 2: Structure Materials, Mechanics and Dynamics of Materials; Chapter 3: Material Science in Biology and Medicine; Chapter 4: Mathematical Methods in Materials Science.